2000
DOI: 10.1046/j.1365-2036.2000.014s2035.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: gall‐bladder motility after intestinal surgery

Abstract: Summary There is a close relationship in humans between gall‐bladder motility and gastrointestinal motility during the fasting state, as well as in the post‐prandial period. Only a minority of publications take this relationship into account in the description of biliary dysmotility after various surgical procedures. Most publications deal with post‐prandial gall‐bladder motility or with stimulation of gall‐bladder contraction from various prokinetic drugs or gastrointestinal hormones. Impaired gall‐bladder mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
0
4
0
1
Order By: Relevance
“…The reasons suggested for this included changes in gallbladder physiological [6] and lithogenic changes in the bile [7]. This high frequency is likely to be related to the surgical dissection of the vagus nerve branches, the use of D1 or D2 lymph node dissections [4,8], and the method used for anatomical gastrointestinal reconstruction (Roux-en-Y or Billroth II) [9][10][11]. There have been some reports of high mortality rates for patients undergoing cholecystectomy for cholecystitis after they have had gastrectomies, because of their poor health status postoperatively (20.0-57.0%) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons suggested for this included changes in gallbladder physiological [6] and lithogenic changes in the bile [7]. This high frequency is likely to be related to the surgical dissection of the vagus nerve branches, the use of D1 or D2 lymph node dissections [4,8], and the method used for anatomical gastrointestinal reconstruction (Roux-en-Y or Billroth II) [9][10][11]. There have been some reports of high mortality rates for patients undergoing cholecystectomy for cholecystitis after they have had gastrectomies, because of their poor health status postoperatively (20.0-57.0%) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported a three-four fold increased incidence 5 years after gastric surgery (up to 15-25 %) [1][2][3][4][5][6] with an estimated mean value of 17 % in all studies [1][2][3][4][5][6][7]. The underlying mechanism was thought to be related to surgical dissection of the vagus nerve branches and the anatomical gastrointestinal reconstruction [5,[8][9][10], and to the extent of gastrectomy and lymphadenectomy [1,4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Eine Hypomotilität der Gallenblase, zum Beispiel im Rahmen einer diabetischen Gastroenteropathie, gilt als Risikofaktor der Gallenblasensteinbildung [6]. Eine verminderte Motilität wird auch bei postoperativen Zuständen wie B-II-Magen, nach Pyloroplastik oder Kolektomie beschrieben [8,10]. Da eine ausreichende Gallenblasenkontraktilität auch Voraussetzung der heute nur in ausgewählten Fällen praktizierten oralen Litholyse-Behandlung ist, sollte somit vor Beginn einer oralen Litholyse eine Funktionssonografie durchgeführt werden [11].…”
Section: Indikationenunclassified